Agrarian Reform Synergy as an Effort to Build a Conducive Investment Climate - R Agus Marhendra; Siti Aminah (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
This research analyzes the synergy between the agrarian reform program and a conducive investment climate in Indonesia, focusing on implementing agrarian reform in South Sulawesi Province. Agrarian reform is essential in reducing inequality in land tenure, resolving agrarian conflicts, and improving community welfare through fair land redistribution. Apart from that, legal certainty over land through the legalization of assets is considered capable of increasing the interest of domestic and foreign investors. This research uses a qualitative approach with data collection methods: in-depth interviews, direct observation, and study of documents related to agrarian reform. Data analysis was carried out descriptively and narratively to understand the relationship between agrarian reform and the investment climate. The research results show that agrarian reform is essential in creating social justice through land redistribution and improving the investment climate by providing legal certainty. However, synergy between the Government, society, and the private sector is necessary to implement agrarian reform effectively. Sound Governance principles, such as transparency and accountability, are essential for preventing agrarian conflicts and building investor confidence. In conclusion, the synergy between agrarian reform and investment policy can catalyze inclusive and sustainable economic growth. Collaboration between parties is the key to creating social stability and investment in Indonesia.